Is the recent increase in long-term interest rates a threat to euro-area recovery? - Grégory Claeys; Konstantinos Efstathiou (Bruegel, 2017)
After reaching historically low levels in the first half of 2016, European long-term sovereign yields experienced a notable increase in the second half of 2016 and at the beginning of 2017, before stabilising in the last few months. The nominal long-term interest rate can be decomposed into the following components: a risk-free rate, various premia to compensate investors for future inflation and potential defaults, and a term premium. All of these components have been on a downward trend over the last few years. But some of these trends might have reversed in the second half of 2016, leading to an increase in long-term yields. Understanding the main factors driving interest rates higher in recent months is important. If the rise in interest rates is driven by good news for the economic outlook for the euro area, it would represent a welcome normalisation of the European situation. However, if higher rates are unjustified by economic fundamentals (ie higher growth and inflation expectations), it would represent an unwarranted tightening of financial conditions that could jeopardise the recovery. In fact, the recent movement in sovereign yields in the euro area has resulted from the combination of several factors: 1) a rise in country-specific risks arising mainly from political uncertainty in some euro-area countries; 2) a revision of market expectations for inflation, growth and the path of future interest rates because of good news about the recovery in the euro area; 3) spill-overs from increasing yields in the US coming from the normalisation of monetary policy by the Fed and a potential fiscal policy shift by the new administration; and 4) an increase in the term premium reflecting uncertainty around markets' expectations. The recent rise is thus mainly driven by good news and does not represent a strong tightening of financial conditions for euro-area households and companies, nor does it currently endanger public finances. Moreover, from an historical perspective (especially when compared to the significant decline in yields over recent decades), the recent rise is of a relatively moderate magnitude and very much similar to previous benign episodes of yield increases (such as in early 2015). The ECB should monitor the situation carefully but it should not be a major concern for the moment. Nevertheless, if in the future sovereign yields from euro-area member states drift away from levels compatible with economic fundamentals, or threaten the European recovery and the return of inflation towards 2 percent (which is not the case at the moment) the EuropeanCentral Bank's expanded toolbox should be sufficient to influence the yield curve.
Keywords: 330